2017
DOI: 10.1186/s12889-016-3951-7
|View full text |Cite
|
Sign up to set email alerts
|

Short sickness absence and subsequent sickness absence due to mental disorders - a follow-up study among municipal employees

Abstract: BackgroundMental disorders are common diagnostic causes for longer sickness absence and disability retirement in OECD-countries. Short sickness absence spells are also common, and neither trivial for health and work ability. We studied how prior short sickness absence spells and days are associated with subsequent longer sickness absence due to mental disorders in two age-groups of municipal employees during a 2-, 5- and 9-year follow-up.MethodsThe analyses covered 20–34 and 35–49-year-old employees of the Cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Short sickness absence spells constitute a large bulk of total sickness absence; by excluding these, we would have excluded a large number of absence days. An earlier study in the present study setting showed that the risk for long sickness absence for mental disorders increased with an increasing number of short sickness absence spells and days 52…”
Section: Methods and Analysismentioning
confidence: 42%
“…Short sickness absence spells constitute a large bulk of total sickness absence; by excluding these, we would have excluded a large number of absence days. An earlier study in the present study setting showed that the risk for long sickness absence for mental disorders increased with an increasing number of short sickness absence spells and days 52…”
Section: Methods and Analysismentioning
confidence: 42%
“…It can also lead to financial strain on companies and society [10]. Furthermore, several short sickness absence spells have been shown to predict later long sickness absence [12] and can also predict premature mortality [13], even when controlling for health status.…”
Section: Introductionmentioning
confidence: 99%
“…Our threshold represents the closest to the upper quartile of the population. It is to be noted that our definition deviates from the more frequently used threshold found in the research literature (three-to-four short-term SA spells/year) (Notenbomer et al 2019;Koopmans et al 2008;Sumanen et al 2017). We expect the high number of short-term SA spells to reflect the employer's policy to allow self-referred SA up until three working days.…”
Section: Predictorsmentioning
confidence: 92%